Biomarkers for prediction of mortality in left-sided infective endocarditis. (July 2020) - Siciliano, Rinaldo F.; Gualandro, Danielle M.; Bittencourt, Marcio Sommer; Paixão, Milena; Marcondes-Braga, Fabiana; Soeiro, Alexandre de Matos; Strunz, Célia; Pacanaro, Ana Paula; Puelacher, Christian; Tarasoutchi, Flavio; Di Somma, Salvatore; Caramelli, Bruno; et al.
Highlights: We explore cardiac/inflammatory biomarkers to predict in-hospital mortality in endocarditis. Troponin concentration measured at admission showed the highest accuracy for mortality prediction. Inflammatory biomarkers had better accuracy at the 7th day than at admission. Abstract: Background: Evidence regarding biomarkers for risk prediction in patients with infective endocarditis (IE) is limited. We aimed to investigate the value of a panel of biomarkers for the prediction of in-hospital mortality in patients with IE. Methods: Between 2016 and 2018, consecutive IE patients admitted to the emergency department were prospectively included. Blood concentrations of nine biomarkers were measured at admission (D0) and on the seventh day (D7) of antibiotic therapy: C-reactive protein (CRP), sensitive troponin I (s-cTnI), procalcitonin, B-type natriuretic peptide (BNP), neutrophil gelatinase-associated lipocalin (NGAL), interleukin 6 (IL6), tumor necrosis factor α (TNF-α), proadrenomedullin, alpha-1-acid glycoprotein, and galectin 3. The primary endpoint was in-hospital mortality. Results: Among 97 patients, 56% underwent cardiac surgery, and in-hospital mortality was 27%. At admission, six biomarkers were independent predictors of in-hospital mortality: s-cTnI (OR 3.4; 95%CI 1.8–6.4; P  < 0.001), BNP (OR 2.7; 95%CI 1.4–5.1; P  = 0.002), IL-6 (OR 2.06; 95%CI 1.3–3.7; P  = 0.019), procalcitonin (OR 1.9; 95%CI 1.1–3.2; P  = 0.018), TNF-α (OR 1.8; 95%CI 1.1–2.9; P  = 0.019), and CRP (OR 1.8; 95%CI 1.0–3.3; P  = 0.037). At admission, S-cTnI provided the highest accuracy for predicting mortality (area under the ROC curve: s-cTnI 0.812, BNP 0.727, IL-6 0.734, procalcitonin 0.684, TNF-α 0.675, CRP 0.670). After 7 days of antibiotic therapy, BNP and inflammatory biomarkers improved their performance (s-cTnI 0.814, BNP 0.823, IL-6 0.695, procalcitonin 0.802, TNF-α 0.554, CRP 0.759). Conclusion: S-cTnI concentration measured at admission had the highest accuracy for mortality prediction in patients with IE.